MODEL PENILAIAN TRANSAKSI PIHAK BERELASI YANG TERINDIKASI TUNNELING: BUKTI EMPIRIS PADA TRANSAKSI PIHAK BERELASI DI INDONESIA - Ratna Chandra Sari (LPPM UNY, 2012)
This study focuses on the expropriation of non-controlling shareholders through tunneling activity. Current study in tunneling still found obstacles in measurement because it is difficult to prove, although tunneling activity going on in business practices. The objective of this is to develop tunneling valuation model. This study defines the tunneling as related party transactions that are used to tunnel out of public companies’ resource for the benefit of the controlling shareholder. Tunneling in this study was divided based on the resources being tunneled that are cash flow tunneling and asset tunneling. The formation a valuation model using data of disclosure of statements affiliate and conflict of interest transactions 2010-2011. Based on the assessment method of tunneling, the transaction is classified as cash flow tunneling as 40.5% and asset tunneling as 34%. The company which announced related party transaction which indicated tunneling obtain negative abnormal return during the announcement of the related party transaction